The effect of idiosyncratic and macroeconomic risk on cash holdings - Kadzima, Marvelous (Department of Finance and Tax, 2023)
The thesis explores the dynamics and determinants of corporate cash holding (or corporate liquidity) in South Africa in three related studies. The first study empirically investigates the sensitivity of corporate cash holdings to changes in idiosyncratic and macroeconomic risk. The analysis is carried out for a panel of South African non-financial firms from 1980 to 2019. Employing the two-step system Generalised Methods of Moments (GMM), results show that South African firms become conservative with their cash when faced with high idiosyncratic risk and reduce cash levels in periods of high macroeconomic uncertainty. In addition, the evidence shows that the impact of both macroeconomic and idiosyncratic risk on corporate cash holdings is more pronounced in financially constrained firms. Overall, the study provides evidence of the role of risk in corporate decisions and gives insight into the firm characteristics that drive the increase in corporate cash holdings. The second study investigates the role of social media in reducing idiosyncratic risk and in enhancing firm liquidity. Specifically, the study explores the individual impacts of Facebook indicators on stock returns, idiosyncratic risk, and stock liquidity. In doing this, the study employs firm-specific Facebook data sourced from Crowd Tangle merged with stock data and financial data of JSE listed firms from 2010 to 2020. Using linear regression and controlling for industry and time fixed effects, results show positive social media sentiments are associated with higher liquidity and lower idiosyncratic risk. However, the volume of social media content is associated with lower liquidity and higher idiosyncratic risk, suggesting that the risk exposure associated with information dissemination offset the benefits of reducing information asymmetry, at least for the sample firms. Further analyses show evidence of the heterogeneous impacts of social media across different types of firms. Overall, the study provides evidence for the role of firm social media activities and public sentiments on stock market performance and highlights social media's predictive and explanatory power in finance. The final study explores the extent to which chief executive officer (CEO) and directors' characteristics impact the probability that a firm adopts social media. Employing logistic regressions on non-financial firms listed on the JSE for 2010 to 2020, the study finds that older directors and executives reduce firms' likelihood of adopting social media. Whereas female directors are positively associated with the probability that firms adopt social media. Further analysis shows that financial resources and business risk may not always make a difference in the influence of director characteristics. While female directors are likely to consider the factors when making social media decisions, the impact of age is not influenced. The study adds to and expand existing literature on board structure and organisational outcomes and offers a novel approach to evaluating the role of directors in firm social media decisions.